Physico-chemical Composition of Two Varieties of Moroccan Palm Date Fruit - Elguerrouj1, M.; Paquot3, M.; Robert3, C.; Benjouad2, A.; Bouakka1, M.; Hakkou1, A. (Asian Journal of Chemistry, 2011)
For human nutrition, palm date fruit may be considered an ideal food, providing an essential nutriment and benefit health for the body. At this moment, few data are available on the composition of palm date fruit grown in Morocco. In this study date, fruit (Phoenix dactylifera L) of two cultivars Aziza Bouzid and Assiane from Morocco were evaluated for the physical and chemical composition. Studied were also conducted on the physicochemical properties of dietary fibre. Weight ranged respectively for Aziza Bouzid and Assiane (5.85 to 6.22 g), volume (5.21 to 5.25 mL) induce that the two cultivars are classified as small fruits varieties, but both of them are good source of sugar (71 to 80 %) and dietary fibre (10.22 to 12.79 %) on a dry matter basis. When Aziza Bouzid contain a significant quantities of some essential amino acid (lysine: 184, isoleucine 122, threonine 98 mg/100 g dry matter), Assiane variety was richer in mineral macro-element (potassium: 863, calcium 87 mg/100 g dry matter). The hydration properties of dietary fibre for Aziza Bouzid and Assiane, respectively (14.90- 15.30 g of water/g sample) and fat absorption capacity (8.6-9.15 g oil/g sample) make palm date fruit a valuable source to be include in the formulation in food.